Novel Synthesis of ZrB2 Powder Via Molten-Salt-Mediated Magnesiothermic Reduction - Zhang, Shaowei; Khangkhamano, Matthana; Zhang, Haijun; Yeprem, Hasibe Aygul (WILEY, 2014)
Zirconium diboride (ZrB2) powder was synthesized at a low temperature via a molten-salt-mediated reduction route using ZrO2, Na2B4O7 and Mg powders as starting raw materials. By using appropriately excessive amounts of Mg and Na2B4O7 to compensate for their evaporation losses, ZrO2 could be completely converted into ZrB2 after 3h at 1200 degrees C. In addition, the formation of undesirable Mg3B2O6 could be effectively avoided. As-prepared ZrB2 powders were phase pure, 300-400nm in size and generally well dispersed. SEM images showed that to a large extent the reactively formed ZrB2 retained the morphology and size of the starting ZrO2. The salt melt formed from MgCl2 and Na2B4O7 at test temperatures is believed to be responsible for the reduced synthesis temperature and good dispersion of the final ZrB2 product powder.
Keywords: ZIRCONIUM DIBORIDE ZRB2; TEMPERATURE; ZRO2; Materials Science